(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the significance and role of speech therapy sessions in the development of children’s speech. It highlights the scientific and methodological foundations for eliminating speech disorders, the methods and technologies of speech therapy, as well as the specific characteristics of sessions conducted with children of different age groups.